2020
DOI: 10.3390/jfmk5030065
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Tissue during Orthodontic Tooth Movement: An Immunofluorescence Study

Abstract: The orthodontic tooth movement is the last step of several biological processes that take place after the application of external forces. During this process, dental pulp tissue is subjected to structural and protein expression modifications in order to maintain their integrity and functional morphology. The purpose of the present work was to perform an in vivo study, evaluating protein expression modifications in the human dental pulp of patients that have undergone orthodontic tooth movement due to pre-calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
3
15
1
Order By: Relevance
“…Vascular volume density at 6 hours, was high but fell after 24 and 72 hours, almost similar to the values in the dental pulp not subjected to orthodontic force (Santamaria Jr et al, 2006). The findings observed in the experimental rats were also mirrored in human cell experiments using haematoxylin-eosin staining (Lazzaretti et al, 2014) and/or immunofluorescence (Vermiglio et al, 2020) analyses. In a clinical study, orthodontic force was applied to the teeth of younger and older subjects via fixed orthodontic appliance, and pulpal blood flow was measured using Laser Doppler flowmetry.…”
Section: Effects Of Orthodontic Treatment On Dental Pulpsupporting
confidence: 69%
See 1 more Smart Citation
“…Vascular volume density at 6 hours, was high but fell after 24 and 72 hours, almost similar to the values in the dental pulp not subjected to orthodontic force (Santamaria Jr et al, 2006). The findings observed in the experimental rats were also mirrored in human cell experiments using haematoxylin-eosin staining (Lazzaretti et al, 2014) and/or immunofluorescence (Vermiglio et al, 2020) analyses. In a clinical study, orthodontic force was applied to the teeth of younger and older subjects via fixed orthodontic appliance, and pulpal blood flow was measured using Laser Doppler flowmetry.…”
Section: Effects Of Orthodontic Treatment On Dental Pulpsupporting
confidence: 69%
“…The application of appropriate or light orthodontic force enables sufficient tooth movement, limits the damage in the dental pulp and allows for the repair of any damage that is developed during orthodontic treatment (Aydin & Er, 2016). This was demonstrated in a recent in vivo study involving human dental pulp where no irreversible iatrogenic changes were observed in the dental pulp following application of appropriate orthodontic forces for tooth movement (Vermiglio et al, 2020). Orthodontic tooth movement is not a direct cause of pulpal necrosis (Consolaro & Consolaro, 2018;Weissheimer et al, 2021) and obliteration of the dental pulp, but when these are observed following orthodontic tooth movement, a previous history of dental trauma could possibly be the aetiological factor (Javed et al, 2015;Yang et al, 2016;Consolaro & Consolaro, 2018).…”
Section: Effects Of Orthodontic Treatment On Dental Pulpmentioning
confidence: 90%
“…Primary antibodies were detected using Texas-Red-conjugated immunoglobulin (IgG) anti-mouse (Jackson ImmunoReseach Laboratories, Inc., West Grove, PA, USA) and Fluorescein Isothiocyanate (FITC) (Jackson ImmunoReseach, Inc., West Grove, PA, USA), both at a dilution range of 1:100 [ 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Light orthodontic force is usually optimum for producing tooth movement, minimizing dental pulp damage, and enabling any pulpal damage repair during orthodontic movement [3] . The occurrence of dental pulp obliteration and/or necrosis after orthodontic movement can indicate a past history of dental trauma as the causative factor, and this requires thorough investigation.…”
Section: Orthodontics and Endodonticsmentioning
confidence: 99%